2020
DOI: 10.1038/s41592-020-00998-0
|View full text |Cite
|
Sign up to set email alerts
|

diaPASEF: parallel accumulation–serial fragmentation combined with data-independent acquisition

Abstract: Data independent acquisition (DIA) modes isolate and concurrently fragment populations of different precursors by cycling through segments of a predefined precursor m/z range. Although these selection windows collectively cover the entire m/z range, overall only a few percent of all incoming ions are sampled. Making use of the correlation of molecular weight and ion mobility in a trapped ion mobility device (timsTOF Pro), we here devise a novel scan mode that samples up to 100% of the peptide precursor ion cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
688
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 569 publications
(697 citation statements)
references
References 50 publications
6
688
2
1
Order By: Relevance
“…To benchmark the performance of the ion mobility module in DIA-NN in combination with the FragPipe-generated libraries, we reprocessed the dia-PASEF reference dataset (Meier et al, 2020), wherein a HeLa tryptic digest was acquired using different injection amounts (10ng -100ng on a Thermo Fisher EASY-nLC 1200 nanoLC, 95-minute gradient) and chromatographic gradient lengths (200ng, 4.8-min to 21-min on an Evosep One microflow system) ( Figure 2a). In the nanoflow experiments, the FragPipe-generated library built from 24 fractionated DDA PASEF runs and filtered at 1% protein and peptide FDR contained 9991 proteins and 161325 peptides (see Table 1 and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To benchmark the performance of the ion mobility module in DIA-NN in combination with the FragPipe-generated libraries, we reprocessed the dia-PASEF reference dataset (Meier et al, 2020), wherein a HeLa tryptic digest was acquired using different injection amounts (10ng -100ng on a Thermo Fisher EASY-nLC 1200 nanoLC, 95-minute gradient) and chromatographic gradient lengths (200ng, 4.8-min to 21-min on an Evosep One microflow system) ( Figure 2a). In the nanoflow experiments, the FragPipe-generated library built from 24 fractionated DDA PASEF runs and filtered at 1% protein and peptide FDR contained 9991 proteins and 161325 peptides (see Table 1 and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Figure S1). We also processed the same dia-PASEF data with DIA-NN using the original spectral libraries (Meier et al, 2020), to quantify the contribution of the FragPipe libraries to the gains in proteomic depth (Supp. Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…1a, b) 24 . These precursors can be fragmented in a highly sensitive manner, either in data dependent (ddaPASEF) or data independent (diaPASEF) mode, resulting in very high ion utilization and data completeness 25 . To explore sensitivity limits, we measured a dilution series of HeLa cell lysate from 25 ng down to the equivalent of a few single cells on a quadrupole time-of-flight instrument (TIMS-qTOF).…”
Section: Noise-reduced Quantitative Mass Spectramentioning
confidence: 99%
“…3c). To achieve high data completeness between hundreds of single-cell measurements, we next replaced ddaPASEF by diaPASEF, in which fragment level matching is further supported by ion mobility data 25 . We found that combining subsequent diaPASEF scan repetitions further improved protein identification numbers.…”
Section: More Than 10-fold Sensitivity Increasementioning
confidence: 99%
“…Compared to developments in sample preparation, MS instrumentation, scan modes and software, the LC apparatus has been largely unchanged in cutting edge MS-based proteomics. While identifications in proteomics experiments have doubled in single-shot experiments this can mainly be traced to improvement on the MS instrumentation and software (12–17). Current trends in LC developments aim rather towards systems for higher throughput and increasing robustness required for clinical applications (18), whereas the race for better separation in single-shot high performance runs with increasingly higher pump pressures has been comparatively abandoned.…”
Section: Introductionmentioning
confidence: 99%